NARRATIVE AND THE POLITICS OF IDENTITY: PATTERNS OF THE SPREAD AND ACCEPTANCE OF RADICALISM AND TERRORISM IN INDONESIA - Firdaus Syam; Sahruddin, Sahruddin; Ajeng Rizqi Rahmanillah (Journal of Social Political Sciences, 2020)
This study aims to examine the narrative map, acceptance and spread patterns, and factors influencing the spread and acceptance of the narrative associated with the phenomenon of radicalism and terrorism in DKI Jakarta Province. It was conducted with a qualitative approach: the data were collected through in-depth interviews with as many as 24 subjects (informants) divided into seven categories, namely, the Rohis (Islamic organization in secondary schools), the LDK (Basic Leadership Training)), mosque youth, youth organizations, religious leaders, da’i (preacher)/ takmir (mosque board), political activists, and cultural leaders. The finding of the study showed that the radicalism narrative has spread through a variety of patterns and has more importantly spread through interpersonal relationship patterns. However, the spread of the narrative has not been accompanied by an acceptance by the respondents of the narrative’s substance. From 96 radicalism and terrorism narratives posed as questions, a total of 62 responses (64.58%) showed opposition to these narratives that are present in the midst of the people of Jakarta. A total of 20% of the respondents expressed an improvement attitude towards the narratives, and the rest were receptive and accepted them with considerations. This finding proves that Jakarta residents not only are relatively free from the influence of radicalism and terrorism narratives but also have an immune system (improvement group) whose numbers among the groups of respondents to the narratives are balanced.